2019
DOI: 10.14740/jmc3399
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Rivaroxaban-Induced Urticaria and Angioedema With Possible Cross-Reaction to Dabigatran

Abstract: Anticoagulants are commonly associated with hemorrhagic complications. However, rare hypersensitivity drug reactions associated with direct oral anticoagulants (DOACs) in form of cutaneous reactions such as urticaria as well as angioedema can have significant burden owing to increase in morbidity and mortality. Angioedema can be allergic, hereditary or idiopathic and can occur in isolation, in combination with urticaria as contributing component of anaphylaxis. With increase in the use of DOACs over warfarin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Interestingly, possible cross-reactivity was previously noted between rivaroxaban and dabigatran. 9 However, mechanisms of this cross-reactivity are not yet fully understood. In contrast to this, dabigatran was identified to be safe for our patient through provocation tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, possible cross-reactivity was previously noted between rivaroxaban and dabigatran. 9 However, mechanisms of this cross-reactivity are not yet fully understood. In contrast to this, dabigatran was identified to be safe for our patient through provocation tests.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1). [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Anaphylaxis secondary to rivaroxaban administration, is a rare condition, estimated to occur in about 0.01% of patients. 20 There are few previous cases of this condition in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Foods, medications, insect stings, and injections of allergen immunotherapy are the most common identifiable causes of anaphylaxis [ 5 , 6 ]. Since the introduction of DOACs to treat VTE and AF, several case reports have been published describing hypersensitivity to rivaroxaban, which is manifested in various forms of skin rashes [ 2 - 4 ]. Anaphylactic reaction following ingestion of rivaroxaban is extremely rare accounting for 0.01% of cases in one study [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of patients with venous thromboembolism (VTE) and atrial fibrillation (AF), direct oral anticoagulants (DOACs) have overshadowed warfarin due to less intracranial bleeding, simplified dosing, and predictable pharmacokinetics compared to warfarin [ 1 , 2 ]. Although, a growing number of reports of adverse drug reactions such as drug eruptions, urticaria, lichenoid eruption, and exanthematous rash have been published [ 2 - 4 ], anaphylaxis due to DOACs is extremely rare. Of 7111 participants in the rivaroxaban treatment arm of the ROCKET-AF study, anaphylaxis was found in 0.01% of cases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Another recently published case report described rivaroxaban-induced urticaria and angioedema, with possible cross reactivity to dabigatran, manifested as rash in a 63-year-old male. 22 There is limited availability of information on the cross reactivity across different DOACs in the literature.…”
Section: Discussionmentioning
confidence: 99%